Predictors of deep-vein thrombosis for acute stroke at admission to a rehabilitation unit: A retrospective study - Li, Fang; Wei, Changkun; Huo, Su; Liu, Xiuzhen; Du, Jubao (Frontiers in Neurology, 2023)
Background: Deep vein thrombosis (DVT) is a common complication of acute stroke (AS). Less studies discussed DVT in patients with AS at admission to rehabilitation unit. The purpose of this study is to identify the predictors of DVT in AS patients admitted to a rehabilitation unit in China. Methods: We retrospectively reviewed the medical records of all patients with AS admitted within 14 days of stroke onset between July 2019 and June 2022 at the Department of Rehabilitation Medicine, Xuanwu Hospital, Capital Medical University, China. Ultrasonography was used to diagnosis DVT in all patients within 3 days after rehabilitation admission. Univariate and binary logistic regression analyses were performed to determine the risk factors for DVT. Results: In all, 234 cases were identified and the incidence rate of DVT among AS patients was 13.2% (31/234). The univariate analysis showed that age, drinking, lower limb muscle strength, Brunnstrom Assessment (BRS), Fugl-Meyer Assessment (FMA), Berg Balance Scale (BBS), Barthel index (BI) scale, serum albumin (Alb) and D-dimer were statistically significant factors. Age (OR=1.037, 95%CI=1.000-1.075, p＜0.05), BBS (OR=0.952, 95%CI= 0.913-0.993, p＜0.05), and D-dimer (OR=1.446, 95%CI= 1.130-1.849, p＜0.05) were demonstrated as independent risk factors for DVT. Conclusion: older age, lower BBS and higher D-dimer levels at rehabilitation admission were independent risk factors for DVT. Therefore, ultrasonography should be performed for those patients with these three significant factors before implementing rehabilitation therapy.